2014
DOI: 10.1002/mabi.201400306
|View full text |Cite
|
Sign up to set email alerts
|

Micropatterning Electrospun Scaffolds to Create Intrinsic Vascular Networks

Abstract: Sufficient vascularization is critical to sustaining viable tissue-engineered (TE) constructs after implantation. Despite significant progress, current approaches lack suturability, porosity, and biodegradability, which hinders rapid perfusion and remodeling in vivo. Consequently, TE vascular networks capable of direct anastomosis to host vasculature and immediate perfusion upon implantation still remain elusive. Here, a hybrid fabrication method is presented for micropatterning fibrous scaffolds that are sutu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 69 publications
0
22
0
Order By: Relevance
“…Another area of recent interest has focused on modifying the manufacturing technique and the actual production of a graft for mechanical testing, with preliminary results showing three histologically distinct layers with distinct burst strength and suture retention profiles, hence setting the groundwork for manipulation of these individual layers for further refinement and manufacturing [58]. Finally, more preliminary work has again taken the advantage of the both the properties of biocompatible scaffolds and the multiple areas in the electrospinning process by utilizing fused deposition modeling to pattern the TEVG along a robust, high-suture retention-property scaffold for use in microvascular networks [59]. Electrospun TEVGs, however, have yet to be implanted in clinical trials.…”
Section: Future Directionsmentioning
confidence: 97%
“…Another area of recent interest has focused on modifying the manufacturing technique and the actual production of a graft for mechanical testing, with preliminary results showing three histologically distinct layers with distinct burst strength and suture retention profiles, hence setting the groundwork for manipulation of these individual layers for further refinement and manufacturing [58]. Finally, more preliminary work has again taken the advantage of the both the properties of biocompatible scaffolds and the multiple areas in the electrospinning process by utilizing fused deposition modeling to pattern the TEVG along a robust, high-suture retention-property scaffold for use in microvascular networks [59]. Electrospun TEVGs, however, have yet to be implanted in clinical trials.…”
Section: Future Directionsmentioning
confidence: 97%
“…This method has been demonstrated to produce both vili-shaped surface relief patterns and 3D woodpile-structured with internal porosity [20,21] . The use of a sacrificial scaffold has also been used in conjunction with electrospinning to produce microporous electrospun mats with internal channels to introduce a prototype vascular network in these scaffolds [22,23] . Recent studies reported on the use of layer-by-layer stereolithography for selectively photocuring Poly-HIPE emulsions to fabricate customised structures with both random microporosity and controlled macroporosity [11,13,24] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, 3D printed poly(vinyl alcohol) (PVA) sacrificial moulds using 3D filament printer have been demonstrated to facilitate fabrication of porous polymeric scaffolds for various tissue engineering applications [23,24]. Ortega et al and Jeffries et al have proposed a new fabrication approach by encapsulating 3D printed single layered PVA channels using an inexpensive 3D filament printer in combination with electrospun nanofibers to create perfusable vascular networks [23,24].…”
mentioning
confidence: 99%
“…Ortega et al and Jeffries et al have proposed a new fabrication approach by encapsulating 3D printed single layered PVA channels using an inexpensive 3D filament printer in combination with electrospun nanofibers to create perfusable vascular networks [23,24]. However, the fabricated scaffolds only comprised a single layer of channels, hence, they didn't generate a functional tissue/organ composed of multiple layers.…”
mentioning
confidence: 99%